(untitled) ("Journal "U". Economy. Management. Finance.", 2025)
The article presents a comprehensive analysis of the concept of working capital and its role in the activities of enterprises. The author identifies the key characteristics and variations of current assets, providing an extensive classification and description of each asset type in this category. In addition, the article examines various interpretations of the concept of working capital by various experts, which made it possible to emphasize its versatility and complexity of structure. The importance of working capital is emphasized through its impact on the overall performance of the company, thereby highlighting it as a fundamental factor in the corporate governance system. Using the example of evaluating the competent management of current assets, the author illustrates that this is a key aspect of financial management that requires a careful approach and strategic planning.